4
$\begingroup$

$$\int_{-{2 π}/3}^{{2 π/3}}-\frac {4\cos(x)}{1 + e^{-4x}} \,\mathrm{d}x $$

I have tried writing this as an even function so I can evaluate:

$$\int_0^{{2π}/3} f_\text{even}(x)\mathrm{d}x$$

But I'm struggling to get to this point as I end up with worse functions that I started with. Any help would be appreciated.

$\endgroup$
  • $\begingroup$ The integral is $-2\sqrt 3$. $\endgroup$ – Maximilian Janisch Nov 14 at 23:01
5
$\begingroup$

Any function $f(x)$ can be decomposed as an even function $g(x) = g(-x)$ and an odd function $h(-x) = -h(x)$ as follows:

\begin{equation} g(x) = \frac{f(x) + f(-x)}{2} \end{equation} and \begin{equation} h(x) = \frac{f(x) - f(-x)}{2}, \end{equation} We can see that $f(x) = g(x) + h(x)$ and $g(-x) = g(x)$ and $h(-x) = -h(x)$ as desired.

Then $\int_{-a}^a f(x) dx = \int_{-a}^a g(x)dx + \int_{-a}^a h(x) dx = 2 \int_{0}^a g(x) dx$.

In your case we have \begin{equation}f(x) = -\frac{4\cos(x)}{1+\exp(-4x)}\end{equation} and \begin{equation} f(-x) = -\frac{4\cos(x)}{1+\exp(4x)} \end{equation} so by our previous definition \begin{align*} g(x) &=-2\cos(x)(\frac{1}{1+\exp(-4x)} + \frac{1}{1+\exp(4x)}) \\&= -2\cos(x)(\frac{(1+\exp(4x)) + (1+\exp(-4x))}{(1+\exp(4x)) (1+\exp(-4x))}) \\&= -2\cos(x), \end{align*} which can be seen by expanding the denominator. Then your integral becomes:

\begin{equation} I = 2\int_0^{2\pi/3} dx ( -2 \cos(x)) = -4 (\sin(x))|_0^{2\pi/3} = -4\sin(2\pi/3) = -2\sqrt{3} \end{equation}

$\endgroup$
  • $\begingroup$ So in the end we are using $\int_{-a}^a f(x)\,dx=\int_{-a}^0 f(x)\,dx+\int_0^a f(x)\,dx=\int_0^a f(-x)\,dx+\int_0^a f(x)\,dx=\int_0^a f(-x)+f(x)\,dx$. $\endgroup$ – Carsten S Nov 15 at 12:01
4
$\begingroup$

Note that,

$$\frac {1}{1 + e^{-4x}} = \frac12+ \frac12 \tanh(2x)$$

Then,

$$\int_{-{2 π}/3}^{{2 π/3}}-\frac {4\cos x}{1 + e^{-4x}} dx = -4\int_0^{{2 π/3}}\cos x dx $$

$\endgroup$
3
$\begingroup$

Your integrand is not an odd function. However, if you define $$ g(x):=\frac12 - \frac1{1+e^{-4x}}=\frac{e^{-4x}-1}{2(e^{-4x}+1)}, $$ you can check that $g(-x)=-g(x)$, i.e. $g$ is an odd function. So your integral now equals $$\int_{-2\pi/3}^{2\pi/3} 4\cos(x)\left[ g(x)-\frac12\right]\,dx,$$ which splits into the integral of an odd function plus the integral of an even function.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.